Improvements in living conditions in Ethiopia between 2000 and 2016: Evidence from Ethiopian Demographic and Health Survey data - Hirvonen, Kalle (International Food Policy Research Institute, 2017)
This research shows how basic living conditions have improved markedly since 2000, albeit somewhat unevenly, with urban areas witnessing the greatest improvements. Still, better access to safe drinking water and proper toilets, together with better housing quality, are indicative that the benefits of economic growth are reaching rural areas.